Targeted inhibition of mecA and agrA genes in clinical MRSA isolates by natural bioactive compounds - Vinodhini, V.; Kavitha, M. (Frontiers in Microbiology, 2025)
IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) colonization in the nasal nares significantly contributes to hospital-acquired infections. This poses a global health concern due to its resistance to β-lactam antibiotics and its virulence mediated by quorum sensing (QS). This study investigates the antimicrobial efficacy of two natural bioactive compounds (BACs)—curcumin and eugenol—against clinical MRSA isolates, specifically focusing on their impact on mecA and agrA gene expression.MethodsNasal swab samples from 150 patients yielded 53 staphylococcal isolates, among which 25 were identified as MRSA. Three highly resistant isolates (VITKV25, VITKV32, and VITKV39), identified as S. aureus through 16S rRNA gene sequencing, were selected for further analysis. The antibacterial efficacy of curcumin, eugenol, and gallic acid was assessed through agar well diffusion and minimum inhibitory concentration (MIC) assays. The presence of mecA and agrA genes was detected using polymerase chain reaction (PCR). Additionally, the impact of these compounds on mecA and agrA gene expression was assessed using Quantitative real-time PCR (qRT-PCR).Results and discussionThe isolates exhibited resistance to multiple antibiotics, including ampicillin, oxacillin, vancomycin, cefoxitin, and erythromycin. Curcumin and eugenol distinctly downregulated mecA and agrA expression levels. In particular, curcumin completely suppressed mecA gene expression in VITKV39 (0.0) and agrA expression in VITKV25 and MRSA (ATCC 43300) (0.0 and 0.1, respectively). Eugenol reduced both genes, mecA and agrA, in VITKV32 to 0.01 and 0.02, respectively. These findings highlight the therapeutic potential of curcumin and eugenol as adjuncts to conventional antibiotics by targeting both resistance and virulence pathways in MRSA.